Fundaments of certain nursing models - Ana Piera Orts (Universidad de Alicante, 1999)
Fundaments of certain nursing models embodied in a naturalistic paradigm (also called phenomenological, humanistic, ethnographical... prototypes) are presented here. A proposal for specific action - a plan for introspective research in nursing - is also shown here.